1994
DOI: 10.1200/jco.1994.12.11.2248
|View full text |Cite
|
Sign up to set email alerts
|

Population study of dihydropyrimidine dehydrogenase in cancer patients.

Abstract: From the present study, it appears that total DPD deficiency is a rare event. Although pretreatment DPD activity cannot be a useful indicator for improving FU dose adaptation strategy, the identification of severe DPD deficiency (< 0.100 nmol/min/mg protein) could lead to starting the treatment with a markedly reduced FU dose or even to using an alternative chemotherapy regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
221
1
13

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(252 citation statements)
references
References 0 publications
16
221
1
13
Order By: Relevance
“…This offers useful themes for undertaking larger prospective pharmacogenetic studies in the future. Regarding DPD deficiency, it is increasingly being recognized as an important pharmacogenetic factor in the aetiology of severe 5-FU associated toxicity (6,18,19). Only one heterozygous subject for this mutation was detected, indicating a low prevalence of the mutation (1.7%) in concordance with previous studies (6).…”
Section: Discussionsupporting
confidence: 86%
“…This offers useful themes for undertaking larger prospective pharmacogenetic studies in the future. Regarding DPD deficiency, it is increasingly being recognized as an important pharmacogenetic factor in the aetiology of severe 5-FU associated toxicity (6,18,19). Only one heterozygous subject for this mutation was detected, indicating a low prevalence of the mutation (1.7%) in concordance with previous studies (6).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, it was also noted that stomatitis occurred more commonly (P < 0.003) in women. Previously, it has been reported that DPD activity is 15% lower in women (Etienne et al, 1994) and this might lead to a gender difference in plasma 5FU concentrations, as described by Vokes et al (1996). Also, in the Vokes study, higher 5FU concentrations were associated with an increase in mucositis.…”
Section: Relationships Of 5fu Concentration Patient Characteristics mentioning
confidence: 80%
“…[48][49][50] In patients who are deficient for DPD, 5-FU clearance is dramatically reduced and standard doses of 5-FU cause excessive toxicity in these patients. 48,51,52 The frequency of DPD deficiency has been estimated to be as high as 2-3% in Caucasians based on measurements of DPD activity in peripheral mononuclear cells in patients and healthy volunteers 53,54 This percentage is probably high enough to justify screening on DPD deficiency prior to 5-FU-based chemotherapy. Instead of screening for specific mutations in the DPYD gene, Mattison et al 55 developed a simple uracil breath test for DPD phenotyping, based on the release of 13 CO 2 from 2-13 C uracil in the presence of intact DPD.…”
Section: -Fluorouracilmentioning
confidence: 99%